A reinterpretation of dinosaur footprints with internal ridges from the Upper Cretaceous Uhangri Formation, Korea - Hwang, Koo-Geun; Lockley, Martin G.; Huh, Min; Paik, In Sung (Palaeogeography, palaeoclimatology, palaeoecology, 2008)
Very unusual dinosaur footprints with radial internal ridges from the Late Cretaceous of southern Korea have been the subject of much controversy. All footprints are in black laminated mudstone/shale, and have gently curved cross-sections that show deformation of a flexible substrate by dinosaur footprint registration. These peculiar patterns have not been recorded at any other site in the world, although natural casts of such features have been reported from a few localities. Each footprint consists of several sectors or pockets partitioned by conspicuous radial ridges. These tracks were first interpreted as sauropod manus-only tracks, supporting Roland Bird's swimming sauropod hypothesis. However, our study casts serious doubt on this theory for two reasons. First, the footprints sometimes exhibit characteristic features such as ungual, digit or heel impressions, suggesting that the mysterious traces are those of a tridactyl, bipedal dinosaur. Second, the unusual tracks are underprints, and the internal ridges are molds of radial cracks on the underside of a sand bed on which large bipeds were walking.